PENGARUH BI RATE, INFLASI, CAR, BOPO, NPL TERHADAP PROFITABILITAS BANK KONVENSIONAL (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2013) - Nilam Maulida Hapsari, 11.05.52.0110; Indarti, MG Kentris (Students' Journal of Accounting and Banking, 2016)
This study aims to examine and analyze the effect of the BI Rate, Inflation, CAR, Operating costs, NPLs of the bank’s, Profitabilty Conventional Banking Companies listed in Indonesia Stock Exchange in 2011-2013. This study uses Signalling Theory. Source data used is secondary data obtained from the Indonesian Stock Exchange. Data analysis techniqueis by using multiple linier regression. Research shows that the variable BI significant positive effect on ROA, Inflation effect but not significant, Capital Adequacy Ratio effect but not significant. Research show that the variable Operating Costs and Non Performing Loan significant negative effect on ROA.Keywords: BI Rate, Inflation, CAR, Operating Costs, NPL, Profitability